Reconceptualizing intercultural competence: A phenomenological investigation of students’ intercultural experiences - Dalib, Syarizan (Elsevier Ltd., 2014)
This paper investigates the notion of intercultural competence from the perspective of students in a Malaysian university.In-depth interviews involving fifteen culturally diverse students were conducted.Students reflected their lived experiences with cultural others and shared their perceptions of competent communication. Using phenomenological analysis of the interview data, two core themes that encompass intercultural competence emerged: acquiring cultural understanding and respecting cultural differences. These core themes indicate that intercultural competence is viewed as a relational process that must include both communication partners to mutually achieve appropriate and effective behaviors.The findings contribute into rethinking the Western perspective by bringing forth a relational perspective into the corpus of intercultural competence.